Carbon Emissions Through the Weathering of Petrogenic Organic Carbon and the Net Geological Carbon Budget of the Tibetan Plateau - Ye Wang; Yang Chen; Shilei Li; David William Hedding; Jun Chen (Geophysical Research Letters)
Abstract Mountain building, alongside the associated erosion and weathering, plays a key role in mediating the long‐term carbon cycle, thus impacting Earth’s climate. Certain processes, such as the weathering of petrogenic organic carbon (OCpetro), still lack comprehensive quantitative research owing to the interference of human activities, hindering a full understanding of the net budget and temporal changes of mountain building. This study explores OCpetro weathering within the Tibetan Plateau by utilizing rhenium as a tracer to quantify OCpetro weathering rates and elucidate carbon fluxes. The overall OCpetro weathering rate and net carbon budget of the Tibetan Plateau are 1.95(±0.60) tC km−2 yr−1 and 1.81+0.34/−0.49 tC km−2 yr−1, indicating the Tibetan Plateau currently serves as a carbon source. This study not only refines our understanding of the OCpetro weathering but also reveals a dynamic transformational impact on the geological carbon cycle from mountain building at different stages.